Platelet-rich plasma in the treatment of Class II furcation defects: a histometrical study in dogs - Fabrícia Ferreira Suaid; Marcelo Diniz Carvalho; Gláucia Maria Bovi Ambrosano; Francisco Humberto Nociti Junior; Marcio Zaffalon Casati; Enilson Antônio Sallum (University of São Paulo, 2012)
OBJECTIVE: This study was designed to evaluate the potential adjunctive benefits of platelet-rich plasma (PRP) when used with guided-tissue regeneration (GTR) and bioactive glass (BG) in the treatment of Class II furcation lesions. MATERIAL AND METHODS: Bilateral Class II furcation lesions were surgically created and allowed to become chronic in the mandibular third premolars of 9 dogs. The defects were randomly assigned to: A) GTR+BG and B) GTR+BG+PRP. Similar defects were created in the maxillary third premolars and received the same treatments after 45 days. Dogs were sacrificed 90 days after the first treatment. The histometric parameters evaluated were: connective tissue adaptation, new cementum, new bone, mineralized bone area, non-mineralized bone area, and residual BG particle area. RESULTS: Data analysis showed a superior length of new cementum and a greater mineralized bone area for group B in both periods (p<0.05). The non-mineralized bone area was greater in the control group (p<0.05) in both periods. CONCLUSION: Within the limits of this study, it can be concluded that the use of PRP in the treatment of Class II furcation defects may enhance the amount of new cementum and provide a more mineralized bone in a shorter period of time.